Plan de mercadeo del producto pelletizado para ganado bovino lechero del taller de procesos de harinas y balanceados de la ESPAM MFL - Párraga Basurto, Jalder Javier (2012)
This research aims to establish a marketing model that allows the Polytechnic Agricultural School of Manabí Manuel Felix Lopez to improve commercial operation of the pelleting plant located in balanced meal workshop. For the development of the thesis we used tools such as surveys and statistical graphs, which allowed diagnose the plant and production real situation in the producers that belong to the Association of ranchers in Bolívar Canton. The plan identified marketing techniques and organization procedure for the product and workshops. It also provides a product under quality standards with a single package, services such as strategic locations for sale and transportation therefore, seeks to capture the attention of producers through advertising campaigns to captureattention. The sale price $ 18.75 in a presentation of 40Kg makes attractive for new markets the same as representing financial benefits in marketing, which is a fundamental alternative not only to achieve further development of the institution, but also technical development of livestock producers in Bolívar canton. This work was socialize to the working staff in the pelleting plant, putting relevance in the importance of using marketing strategies and presentation of the proposal which carries a unique brand and packaging. As a result there was commitment and willingness on the part of the university and the plant personnel.